Hyoscine versus diazepam for the management of true vertigo in the emergency department - Kariman, Hamid; Vajihi, Firoozeh; Amini, Afshin; Shahrami, Ali; Arhami-Dolatabadi, Ali; Shojaee, Majid; Baratloo, Alireza (Bangladesh Journal of Pharmacology, 2017)
The present study was a double-blind clinical trial to compare the efficiency of hysocine and diazepam in vertigo treatment. Eligible patients (n=69) were randomly divided into 2 groups of 5 mg hyoscine and 10 mg diazepam. Severity of vertigo was measured in supine and sitting position, and while turning the head. Vertigo severity was assessed before, and 1 and 2 hours after administration of the drug. Treatment success rate of diazepam in relieving vertigo in different positions varied between 88.9 and 100%, while this rate was 31.273.5% in hyoscine treatment group (p<0.01). Prescription of diazepam led to complete relief of vertigo in 4063% of the patients, while this rate was only 2.612.5% in hyoscine treatment group (p<0.001). It is likely that diazepam is a better option than hyoscine for management of true vertigo in patients presenting to the emergency department.